Chemical Enhancement Effect of Icotinib-Au Complex Studied by Combined Density Functional Theory and Surface-Enhanced Raman Scattering - Lian, Shuai (Langmuir : the ACS journal of surfaces and colloids, 2021)
Icotinib is an epidermal growth factor receptor tyrosine kinase inhibitor used in the treatment of non-small cell lung cancer. The charge transfer effect between gold nanoparticles (AuNPs) and icotinib molecules can be used as a model to study the adsorption mechanism between molecules and metal. The adsorption of icotinib on the AuNP surface was confirmed by UV-vis and transmission electron microscopy (TEM) experiments. To explain the nature of chemisorption between icotinib and AuNPs from a theoretical perspective, the molecular correlation properties of the complex model of icotinib-Au6 were studied by the density functional theory method. By studying the molecular electrostatic potential of an icotinib molecule, four potential binding sites of the icotinib molecule were predicted. The calculation results of binding energy showed that the complex formed by chemisorption of icotinib through acetylene group and Au6 was the most stable one. The molecular frontier orbitals of icotinib and icotinib-Au6 confirmed that the charge transfer effect occurred on the acetylene group, benzene ring, and quinazoline ring of the icotinib molecule. The Herzberg-Teller surface selection rule was used to explain selective enhancement in the theoretically calculated Raman spectra. By comparing the spectra of theory and experiment, the cause of spectral peak shift and broadening that appeared in the surface-enhanced Raman scattering spectrum compared with the normal Raman spectrum was explained as well. This work would contribute to the development and application of the icotinib-Au drug carrier system